2020
DOI: 10.1161/hypertensionaha.119.13698
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine, Via A 2B Receptors, Inhibits Human (P-SMC) Progenitor Smooth Muscle Cell Growth

Abstract: c-Kit+ progenitor smooth muscle cells (P-SMCs) can develop into SMCs that contribute to injury-induced neointimal thickening. Here, we investigated whether adenosine reduces P-SMC migration and proliferation and whether this contributes to adenosine's inhibitory actions on neointima formation. In human P-SMCs, 2-chloroadenosine (stable adenosine analogue) and BAY60-6583 (A2B agonist) inhibited P-SMC proliferation and migration. Likewise, increasing endogenous adenosine by blocking adenosine metabolism with ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Extracellular purines play a significant role in cardiovascular system homeostasis. Adenosine that is abundantly produced on the surface of endothelial and vascular smooth muscle cells by ecto-nucleotidases, dampens via P1 receptors endothelial activation, immune cell adhesion, smooth muscle cell proliferation and foam cell formation that all together initiate and drive atherosclerotic process in the vessel wall [ 4 , 107 , 108 , 109 , 110 ]. Under stress conditions related to atherosclerosis, such as hypoxia, depressed cellular energy state lead to acute increase and release of adenosine from the cell [ 111 ].…”
Section: Cardiovascular Pathologies Associated With Increased Ada mentioning
confidence: 99%
“…Extracellular purines play a significant role in cardiovascular system homeostasis. Adenosine that is abundantly produced on the surface of endothelial and vascular smooth muscle cells by ecto-nucleotidases, dampens via P1 receptors endothelial activation, immune cell adhesion, smooth muscle cell proliferation and foam cell formation that all together initiate and drive atherosclerotic process in the vessel wall [ 4 , 107 , 108 , 109 , 110 ]. Under stress conditions related to atherosclerosis, such as hypoxia, depressed cellular energy state lead to acute increase and release of adenosine from the cell [ 111 ].…”
Section: Cardiovascular Pathologies Associated With Increased Ada mentioning
confidence: 99%
“…Briefly, ADOR-A2B signaling leads to activation of adenylyl cyclase leading to augmentation of cAMP and PKA; PKA subsequently inhibits proliferation by blocking several pathways (ERK1/2, Akt and Skp2) that converge at Cyclin D with the collective result being diminished G1 cyclin expression and reduced cell cycle progression as a result (11). This mechanism is also maintained in circulating progenitor SMCs, another documented source of NI proliferation (5,12). The role of adenosine and circulating progenitors is also supported by rescue of the observed effects by wild type bone marrow transplant in ADOR-A2B knockout mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine signals primarily via 4 receptors with preclinical work suggesting a potential role for adenosine receptor (ADOR)-A2B in the regulation of the vascular effects observed, particularly NI proliferation (10). Indeed, in vitro and in vivo arterial injury models supports adenosine mitigating NI formation via ADOR-A2B-mediated inhibition of SMC proliferation (11)(12)(13). Despite this promising preclinical work, ADO has yet to establish itself as a viable therapeutic approach for ISR, owing in part to its innate limitations, particularly its short half-life (7)(8)(9)14).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular muscle cell proliferation is an important component of vascular remodeling which is regulated partly through A 2B receptors [148] and it was shown that activation of A 2B R protects against vascular injury [149].…”
Section: Adenosine and Vascular Injury And Repairmentioning
confidence: 99%